Dystrophin‐deficient muscular dystrophy in two lurcher siblings. (27th January 2015) - Giannasi, C.; Tappin, S.W.; Guo, L.T.; Shelton, G.D.; Palus, V.
<x xml:space="preserve">Abstract</x> Two cases of dystrophin‐deficient muscular dystrophy in 16‐week‐old male lurcher siblings are reported. The myopathies were characterised by regurgitation, progressive weakness and muscle wastage. The dogs had generalised weakness in all four limbs, with more pronounced weakness in the pelvic limbs. Reduced withdrawal in all limbs, muscle contracture and lingual hypertrophy were noted. Serum creatine kinase activities were markedly elevated. Electromyographic abnormalities included fibrillation potentials. Histopathological and immunohistochemical staining were consistent with dystrophin‐deficient muscular dystrophy. Clinical improvement was noted in one of the cases with l‐carnitine supplementation and supportive therapy. Genetic transmission of the disease was postulated as the dogs were siblings.